VD_FINDINFO HC / 2013 / 48 vom 20. Dezember 2012 - VD Tribunal cantonal (2012)
CONSTRUCTION ET INSTALLATION, DOMMAGES-INTÉRÊTS, PRESCRIPTION, RÉDUCTIONEN GÉNÉRAL | 679 CC, 127 CO, 42 al. 2 CO, 43 al. 1 CO, 60 CO